Description of Muscotabanus gen. nov. and Muscotabanus rafaeli sp. nov. (Diptera: Tabanidae: Diachlorini) from Amazon Basin, Brazil - Augusto Loureiro Henriques; Tiago Kutter Krolow (Memorias do Instituto Oswaldo Cruz, 2013)
A new genus of Tabanidae mimetic of flies is described: Muscotabanus new genus, Muscotabanus rafaeli new species, based on 12 females collected in the state of Amazonas, Brazil. It is presented a discussion for separating the new genus from Diachlorini species which resemblance with sarcophagids flies. It is characterised by striped thorax, banded abdomen, long slender palpus subequal antenna length, labella predominantly membranous, except for a narrow sclerotised plate, basicosta bare, wing hyaline and stigma brown.